2021
DOI: 10.3389/fonc.2021.722743
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Perioperative Dexmedetomidine in Ovarian Cancer: An In Vitro and Xenograft Mouse Model Study

Abstract: BackgroundThe surgical stress response (SSR) causes immunosuppression which may cause residual tumor growth and micrometastasis after cancer surgery. We investigated whether dexmedetomidine affects cancer cell behavior and immune function in an ovarian cancer xenograft mouse model.MethodsThe effect of dexmedetomidine on cell viability and cell cycle was assessed using SK-OV-3 cells at drug concentrations of 0.5, 0.1, 5, and 10 µg mL-1. BALB/c nude mice were used for the ovarian cancer model with the Dexmedetom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…For instance, it was suggested that patients who received propofol and sevoflurane in general anesthesia were associated with better overall survival than those who received desflurane alone ( 2 ). Although DEX has been shown to promote tumorigenesis in neurogliomas and lung carcinomas, breast cancer, and colon cancers ( 12 , 27 ), others suggested that DEX could lower the tumor weight and tumor burden in xenograft mice with ovarian cancer ( 28 ), and repressed esophageal cancer cell proliferation in vivo ( 29 ). Despite the controversial in vivo results, the effect of DEX on long-term survival and tumor recurrence after laparoscopic resection of colorectal cancer has not been evaluated in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was suggested that patients who received propofol and sevoflurane in general anesthesia were associated with better overall survival than those who received desflurane alone ( 2 ). Although DEX has been shown to promote tumorigenesis in neurogliomas and lung carcinomas, breast cancer, and colon cancers ( 12 , 27 ), others suggested that DEX could lower the tumor weight and tumor burden in xenograft mice with ovarian cancer ( 28 ), and repressed esophageal cancer cell proliferation in vivo ( 29 ). Despite the controversial in vivo results, the effect of DEX on long-term survival and tumor recurrence after laparoscopic resection of colorectal cancer has not been evaluated in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…DEX is widely used in the perioperative period and plays a beneficial role in resection of a variety of solid cancers [ 35 ]. A recent animal experiment confirmed its anti-inflammatory effects and showed a lower tumor burden [ 36 ].Clinical researches also shown that application of DEX could reduce serum levels of inflammatory factors in patients receiving carcinoma resection including colon cancer [ 37 ], hysterectomy [ 38 ], and radical gastrectomy [ 39 ]. In addition, immunosuppression attenuated by DEX could also concerned with better outcomes of postoperative cognitive function [ 40 ], effective perioperative analgesia, less use of opioids [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…DEX can effectively inhibit the activation of IGF2 signal pathway, improve the immune function of ovarian cancer rats, inhibit the invasion and migration of ovarian cancer cells, and significantly increase the percentage of CD4 + , CD8 + and the ratio of CD4+/CD8+ ( Tian et al, 2019 ). The DEX infusion may improve the surgical outcomes of ovarian cancer by inhibiting the surgical stress response and the release of stress mediators ( Shin et al, 2021 ). CD3 + T cells and CD4+/CD8+ in DEX group were significantly higher than that in the control group, which could reduce the perioperative inflammatory response and improve the cellular immune function of patients undergoing thoracoscopic radical resection of lung cancer ( Kong and Lu, 2018 ; Zong et al, 2021 ).…”
Section: Dex's Regulatory Effect On Immune Cells and Inflammationmentioning
confidence: 99%